SISTEM PENDIDIKAN, MITIGASI BENCANA DAN STRATEGI PONDOK PESANTREN AL-HASANI KOTA PONTIANAK PADA MASA PANDEMI COVID-19 - Khamim Khamim; Anik Cahyowati; Rizky Adithya; Muhammad Lutfi Hakim (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: The government implemented an online learning system for all elements of education in Indonesia during the Covid-19 pandemic. However, this policy is not implemented in traditional educational institutions such as pesantren. This paper describes the education system, disaster mitigation and strategies of the Al-Hasani Islamic Boarding School Pontianak City during the Covid-19 pandemic. This study uses a field research type and uses interviews and documentation as to its data collection techniques collected from July to September 2021. There are three results in this paper. First, Al-Hasani Islamic Boarding School continues to implement a face-to-face education system (Offline) while still implementing health protocols during the Covid-19 pandemic. Second, Al-Hasani Islamic Boarding School carried out the last two stages well of the three stages that should be implemented in every educational institution, namely planning and sustainability (except preparation) properly. It is proven that none of the students, educators and education staff at the Al-Hasani Islamic Boarding School has confirmed Covid-19 since it first appeared in West Kalimantan until now. Third, there are two strategies carried out by Al-Hasani Islamic Boarding School to stay afloat during the Covid-19 pandemic, namely maintaining cleanliness according to the Arabic proverb and opening a business in the form of gallon water. This last strategy was used by the management of the Al-Hasani Islamic Boarding School to cover the shortcomings of the costs needed for the needs of students and their learning system. Keywords: Education System, Disaster Mitigation, Strategy, Boarding School, Covid-19.